Long-term CD4+ cell count in response to combination antiretroviral therapy. - Paula M Luz; Beatriz Grinsztejn; Luciane Velasque; Antonio G Pacheco; Valdilea G Veloso; Richard D Moore; Claudio J Struchiner (PLoS ONE)
Objective There is a continuous debate on how to adequately evaluate long-term CD4+ cell count in response to combination antiretroviral therapy (ART) among human immunodeficiency virus (HIV)-infected individuals. Our study evaluated the long-term CD4+ cell count response (up to ten years) after initiation of ART and described the differences in the CD4+ cell count response stratified by pretreatment CD4+ cell count, and other socio-demographic, behavioral, and clinical factors. Methods The study population included patients starting ART in the clinical cohorts of Rio de Janeiro, Brazil, and Baltimore, United States. Inverse probability of censoring weighting was used to estimate mean annual CD4+ cell counts while adjusting for choice of initial ART regimen, ART discontinuation and losses-to-follow-up. Results From 1997 to 2011, 3116 individuals started ART; preferred initial regimen was NNRTI-based (63%). The median follow-up time was 5 years, 10% of the individuals had nine or more years of follow-up. Observed CD4+ cell counts increased throughout the ten years of follow-up. Weighted results, in contrast, increased up to year four and plateaued thereafter with 50% of the population reaching CD4+ cell counts of 449/μL or more. Out of all stratification variables considered, only individuals with pre-treatment CD4+ cell counts ≥350/μL showed increasing CD4+ cell counts over time with 76% surpassing the CD4+ cell count >500/μL threshold at year ten. Conclusion The present study corroborates the growing body of knowledge advocating early start of ART by showing that only patients who start ART early fully recover to normal CD4+ cell counts.